105k views
3 votes
How do you derive the lens maker's equation? ...?

User Ledonter
by
8.0k points

1 Answer

4 votes

Using Snell’s law ( n1 sin θi = n2 sin θr ) at point A gives


1) sin i1 = n sin r1

2) i1 = n r1

3) i1 = α1 + β1

4) r1 = β1 - γ

5) α1 + β1 = n(β1 - γ)

6) sin i2 = n sin r2

7) i2 = n r2

8) i2 = α2 + β2

9) r2 = β2 + γ

10) α2 + β2 = n(β2 + γ)

11) α1 + α2 = (n - 1)(β1 + β2)

12) 1/s + 1/s' = (n - 1)(1/R1 + 1/R2)

13) 1/f = (n - 1)(1/R1 - 1/R2)

14) 1/s + 1/s' = 1/f

User Gamerkore
by
7.4k points